2018
DOI: 10.3390/nu10101339
|View full text |Cite
|
Sign up to set email alerts
|

An 8-Week, Low Carbohydrate, High Fat, Ketogenic Diet Enhanced Exhaustive Exercise Capacity in Mice Part 2: Effect on Fatigue Recovery, Post-Exercise Biomarkers and Anti-Oxidation Capacity

Abstract: A low-carbohydrate, high-fat ketogenic diet (KD) is a nutritional approach ensuring that the body utilizes lipids. In our previous study, we found that an eight-week ketogenic high-fat, low-carbohydrate diet increased the capacity of endurance exercise in mice without aggravated muscle injury, despite the decrease of absolute muscle volume. The potential mechanism is most possibly to be enhanced capacity to mobilize and utilize fat. In the present study, we investigated whether a ketogenic diet influences post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 75 publications
(89 reference statements)
4
42
0
Order By: Relevance
“…Similarly, motor performances were improved in all studies, regardless of potential associated cognitive benefits. These results are consistent with many mouse studies demonstrating that keto-adaptation enhanced the capacity to transport and metabolize fat as well as motor abilities and recovery [39][40][41].…”
Section: Cognitive and Motor Impact Of Kd/kssupporting
confidence: 92%
“…Similarly, motor performances were improved in all studies, regardless of potential associated cognitive benefits. These results are consistent with many mouse studies demonstrating that keto-adaptation enhanced the capacity to transport and metabolize fat as well as motor abilities and recovery [39][40][41].…”
Section: Cognitive and Motor Impact Of Kd/kssupporting
confidence: 92%
“…In fact, we have reported in our previous study that KD may reduce muscle damage, as evidenced by lowering damage markers such as creatine kinase (CK) and lactate dehydrogenase (LDH) caused by exhaustive exercise [ 10 ]. We have also reported that 24 h after exercise, a KD contributed to fast recovery from fatigue, where muscle damage was also relieved [ 27 ]. In this vein, the present study purports that KD may contribute to muscle damage prevention and fatigue recovery by adjusting IL-6 secretion profiles.…”
Section: Resultsmentioning
confidence: 99%
“…Since our previous report indicated the amount of fatty acid and triglyceride consumption were enhanced in KD mice, we have herein examined the association between IL-6 and enhanced lipolysis. As discussed previously, a KD has been investigated as a low-carbohydrate nutritional approach within athletic nutrition to performance enhancement, but controversial conclusions have been obtained [ 10 , 26 , 27 ]. In our previous studies, we reported that an eight-week, low-carbohydrate, ketogenic diet increased running time until exhaustion in male C57BL6/J mice, and suggest the mechanism to be an enhanced fat utilization [ 10 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced fat and ketone body utilization involves altered intramuscular triacylglycerol storage and mobilization from adipose tissues and transportation, oxidation, and lipolysis in different muscle fibers via circulation (Huang, Ma, Tominaga, Suzuki, & Liu, ). Accordingly, KD plays a role in modulating muscle‐generated, exercise‐induced pro‐inflammatory cytokines, systemic gluconeogenesis and re‐lipogenesis, interleukin‐6 (IL‐6) and nonesterified fatty acid in blood, enhancing lipolysis and muscle strength.…”
Section: Kd and Musclementioning
confidence: 99%